Reconstruction Criminal Sanctions against Criminal Acts of Corruption based on Justice Value - Ismaidar Ismaidar (Budapest International Research and Critics University, 2021)
During the past ten years, there have been no effective efforts to eradicate corruption. This is a very ironic thing, considering that the aim of the reform is the eradication of Corruption, Collusion, and Nepotism. It also shows that a more democratic government is not serious about combating corruption. That corruption is a crime phenomenon that undermines and impedes the implementation of development so that its prevention and eradication must be prioritized. This paper to analyze the true sanctions against the perpetrators of corruption which are currently not fair, to analyze the weaknesses of sanctions against the current perpetrators of corruption, and to find a reconstruction of sanctions for perpetrators of corruption based on justice. The results of the author's research in the reconstruction of Article 2 paragraph (1) of the Republic of Indonesia Law Number 31 of 1999 Concerning Eradication of Corruption are as follows